Curriculum Supervision in Post-Basic Education and Career Development (PBECD) in Nigeria - Ernest Ohiosmua Ohibime; Zakari Adamu; Victor Olugbenga AYOKO (International Journal on Integrated Education, 2023)
This paper examined the challenges facing curriculum supervision in Post-Basic Education and Career Development (PBECD) in Nigeria. Secondary data were used to provide empirical support for the paper. Data were collected from both print materials and online publications. The paper identified poor funding, inadequate transportation facilities, shortage of curriculum Supervisor, insecurity, poor capacity building programme, inadequate supervision materials, poor communication and poor human relations as some of the challenges that have militated against effective curriculum supervision in the Nigerian Post-Basic Education and Career Development (PBECD). To address these challenges, the paper recommended adequate funding of curriculum supervision at the Nigerian Post-Basic Education and Career Development (PBECD).